Molecular characterization and spatial distribution of dicarboxylic acids and related compounds in fresh snow in China. (15th December 2021) - Zhang, Zhimin; Zhao, Wanyu; Hu, Wei; Deng, Junjun; Ren, Lujie; Wu, Libin; Chen, Shuang; Meng, Jingjing; Pavuluri, Chandra Mouli; Sun, Yele; Wang, Zifa; Kawamura, Kimitaka; et al.
Abstract: Low molecular weight organic compounds are ubiquitous in the atmosphere. However, knowledge on their concentrations and molecular distribution in fresh snow remains limited. Here, twelve fresh snow samples collected at eight sites in China were investigated for dicarboxylic acids and related compounds (DCRCs) including oxocarboxylic acids and α-dicarbonyls. Dissolved organic carbon (DOC) concentrations in the snow samples ranged from 0.99 to 14.6 mg C L −1 . Concentrations of total dicarboxylic acids were from 225 to 1970 μg L −1 (av. 650 μg L −1 ), while oxoacids (28.3–173, av. 68.1 μg L −1 ) and dicarbonyls (12.6–69.2, av. 31.3 μg L −1 ) were less abundant, accounting for 4.6–8.5% (6.2%), 0.45–1.4% (0.73%), and 0.12–0.88% (0.46%) of DOC, respectively. Molecular patterns of dicarboxylic acids are characterized by a predominance of oxalic acid (C2 ) (95.0–1030, av. 310 μg L −1 ), followed by phthalic (Ph) (9.69–244, av. 69.9 μg L −1 ) or succinic (C4 ) (23.8–163, av. 63.7 μg L −1 ) acid. Higher concentrations of Ph in snow from Beijing and Tianjin than other urban and rural regions suggest significant emissions from vehicular exhausts and other fossil fuel combustion sources in megacities. C2 constituted 40–54% of total diacids, corresponding to 1.5–2.6% of snow DOC. The total measured DCRCs represent 5.5–10% of snow DOC, which suggests that there are large amounts of unknown organics requiring further investigations. The spatial distributions of diacids exhibited higher loadings in megacities than rural and island sites. Molecular distributions of diacids indicated that the photochemical modification was restrained under the weak solar radiation during the snow events, while anthropogenic primary sources had a more significant influence in megacities than rural areas and islands. Highlights: Dicarboxylic acids and related compounds were analyzed in urban, rural and island snow samples. Total measured dicarboxylic acids and related compounds represent 5.5–10% of snow DOC. High abundance of phthalic acid in urban snow suggests strong emission from fossil fuel combustion.